Determinants of Bancassurance Adoption in Emerging Economies: Qualitative Evidence from Uganda - Mpaata, Eva; Mindra, Rachel; Oula, Denis Ignatius (Journal of Economics and Behavioral Studies, 2020)
This study was conducted to establish the determinants of bancassurance adoption in emerging economies. The research adopted a qualitative approach based on interviews as a main form of data collection. The study pursued an inductive approach in order to generalize the results. In the analysis process, NVIVO software was used to analyze in detail the different qualitative responses obtained from the data collection phase. The research concentrated primarily on urban Kampala, which is endowed with the majority of commercial banks. This study provides a good insight into the factors (both internal and external) banks consider essential while providing the bancassurance service. As a result other prospect banks can be guided by these factors in their need to provide the bancassurance service. The research explores the supply side of the determinants banks focus on while providing bancassurance. This is new as the majority of studies take a look at the banks’ demand-side perspective. In addition, the challenges faced by banks in offering bancassurance while providing alternatives to prospective banks are being included in the adaptation of bancassurance. The research is purely qualitative as opposed to most previous findings, which are either solely quantitative or partly quantitative and partly qualitative with respect to the determinants of the adoption of bancassurance. Specifically, the focus on bancassurance research in Uganda is also new and original, since bancassurance is new in Uganda.